Smart Cart With Multi-shopping Solutions - Faisal, Tarig; Awawdeh, Moath; Habte, Daniel; Berhanu, Hala; Kifle, Kibrom; Misghina, Lia; Bashir, Anees (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Consumerism has constantly been growing, and visiting marketplaces and purchasing is a key development factor for the economic development of a city. The spending habits of people are a reflector of many development indices. As people go out for purchasing in malls for shopping essential items, they often tend to find long queues at the billing counter, and the queues are more longer during weekends and during sale seasons. This has been deterring people from going out shopping and instead resort to online shopping. This has affected the sales and revenue of departmental chains. Also, people spend quite a considerable amount of time searching through rows in order to find the items of their choice. Proposing a solution to these above-mentioned problems using technology is a real boon. Installing a payment option on the cart itself would result in cutting down the waiting times in queues. Moreover, the customers can also benefit from navigation through the virtual maps that would be displayed on the screens of the carts. This reduces the time wasted by customers in searching for products. Hence the customers are self-dependent during their shopping. For the retail group, their transactions and management are truly simplified with these developments. Additionally, the counter labor will decrease if not cease to zero, which in turn reduces the labor cost drastically. In times of pandemic like now, people have been sticking with online shopping due to various reasons, but they long to go out and spend time in the malls as they would in normal times. The proposed solution would definitely assist in the normalization of lives and bring back on-ground retail back to life.